PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IX-3 SMP NEGERI 3 TEBING TINGGI - Sipayung, Bungaria (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
The purposes of this research is to improve learning result on the application of craft processing aspect through demonstration method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IX-3, Junior High School State 3 Tebing Tinggi which amounted to 38 students. This study used a qualitative descriptive analysis technique. The results showed that the use ofdemonstrationmethod can improve learning result on the application of craftwhich characterized by increased mastery learning students, namely cycle I(81,57%), the cycleII(89,47%) and complete learn the clasical equal to % in cycle II. Key Word : Craft, Demonstration, Learning Result